The 21st Century Handbook of Clinical Ovarian Cancer - Tewari, Krishnansu S.; Monk, Bradley J. (Springer International Publishing : Imprint: Adis, 2015)
A thorough review on ovarian cancer, treatment guidelines and emerging therapies available for the disease. The book was originally commissioned due to recent developments in therapies for ovarian cancer. This concise pocket book will review ovarian cancer's epidemiology, clinical features, diagnosis and medical management. Busy healthcare professionals will benefit from this text, which will not only cover the foundation of ovarian cancer management, but discuss up-to-date national and international treatment guidelines and upcoming therapies.